Retrieval practice enhances learning in real primary school settings, whether distributed or not - Franzoi, Laura; Cembrani, Veronica; Mulatti, Claudio; Treccani, Barbara (Frontiers in Psychology, 2025)
With the aim of bridging the gap between laboratory studies and real-world learning experiences, this research investigated the effects of combining retrieval and distributed practice in primary school settings. Retrieval and distributed practice were implemented through a testing procedure that provided accuracy feedback on students' retrieval attempts until they achieved 100% correct answers, and a spacing procedure that lengthened the interval between the initial reading of the study topic (complex school-like materials, i.e., history texts) and the subsequent study session, respectively. In line with existing literature, our findings support the advantage of the testing procedure over the simple re-reading of the material for enhancing 5th graders' learning. In contrast, the manipulation of the spacing interval did not yield a significant effect on students' performance, suggesting the need to explore other sustainable approaches to implement distributed practice. Our results have important implications for educational practice, emphasizing the need to spread knowledge of evidence-based strategies to foster students' text comprehension and long-term retention.